2015
DOI: 10.1016/j.optmat.2014.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of newly flux grown and highly Yb3+-doped cubic RE2O3 (RE=Y, Gd, Lu) laser crystals

Abstract: We have developed laser grade and highly Yb 3+-doped cubic rare-earth sesquioxides (RE 2 O 3 , RE = Y, Gd, Lu) single crystals by means of a newly designed high-temperature solution growth method which gives them spectroscopic properties different from those obtained by high-temperature solidification methods. Absorption and emission cross sections, visible anti-Stokes emission, fluorescence decays of the new cubic Gd 2 O 3 :Yb 3+ single crystals are presented and compared to those of Y 2 O 3 :Yb 3+ and Lu 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, the resulting integrated absorption crosssection is only a little bit higher in the glass ceramics than in the rareearth sesquioxide single crystals. Note also that the forced electric dipole contribution to the 2 F 7/2 ↔ 2 F 5/2 transition oscillator strength, f fED / f MD ≈9.4, is intermediate between the one found in flux-grown Gd 1.72 Yb 0.28 O 3 (∼11) and Y 1.87 Yb 0.13 O 3 (∼8.8) crystals [24,56,57], which means the covalency of the bonds in the neighborhood of Yb 3+ cations in the glass ceramics compares more favourably with that of the Y 2 O 3 matrix than that of the Gd 2 O 3 or Lu 2 O 3 (∼8.4) matrices. Fig.…”
Section: Glassmentioning
confidence: 73%
See 1 more Smart Citation
“…However, the resulting integrated absorption crosssection is only a little bit higher in the glass ceramics than in the rareearth sesquioxide single crystals. Note also that the forced electric dipole contribution to the 2 F 7/2 ↔ 2 F 5/2 transition oscillator strength, f fED / f MD ≈9.4, is intermediate between the one found in flux-grown Gd 1.72 Yb 0.28 O 3 (∼11) and Y 1.87 Yb 0.13 O 3 (∼8.8) crystals [24,56,57], which means the covalency of the bonds in the neighborhood of Yb 3+ cations in the glass ceramics compares more favourably with that of the Y 2 O 3 matrix than that of the Gd 2 O 3 or Lu 2 O 3 (∼8.4) matrices. Fig.…”
Section: Glassmentioning
confidence: 73%
“…When we compare these numbers, as well as the shape of the spectra, with those of heavily Yb 3+ -doped rare-earth sesquioxides crystals [24,56,57], and among them more particularly (Gd,Yb) 2 O 3 crystals, we see that the Yb 3+ 2 F 5/2 radiative lifetime in the glass ceramics is much shorter than in the rare-earth sesquioxide single crystals. The main reason for this is that the 1 → 6 and 1 → 7 optical transitions (in the notations of [57]) have a peak cross-section much higher in the crystals than in the glasses. Needless to say, the broadness of the absorption bands is higher in the glass ceramics spectra than in the crystals' ones.…”
Section: Glassmentioning
confidence: 96%
“…Four dominant elements that can make easily solid solutions with BaZrO 3 were observed through GDMS and SIMS analysis: Ca, Ti, Sr and Hf, whereas other foreign elements contents are drastically decreased compared to their initial content in the raw material. This highlights that optical floating zone method is a suitable technique for removing foreign impurities from oxide crystals contrary to oxide crystals classically grown with a highly polluting environment, such as refractory ceramics and metallic crucibles, inducing a higher impurities contents with the same or a higher raw material purity [68][69][70]. Optical measurements performed on BaZrO 3 While it is demonstrated that BaZrO 3 solubility is poor in BaB 2 O 4 flux, this self-flux growth approach makes possible to crystallize this highly refractory material at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, cooperative processes between Yb 3+ and Er 3+ ions are believed to be responsible for emission in the regions of 409 [28] and 550 [29,30] nm, as well as in the range 650 - 680 nm [29,31]. The emission in the region of 490 nm is related to the cooperative luminescence of Yb 3+ - Yb 3+ clusters at the doubled Yb 3+ luminescence frequency [32,33] or to cooperative processes between Yb 3+ and Tm 3+ ions [34,35]. Similar spectra were obtained in Yb 3+ : Y 2 O 3 ceramics in [36].…”
Section: Study Of Laser Propertiesmentioning
confidence: 99%